The value of intraovarian autologous platelet rich plasma in women with poor ovarian reserve or ovarian insufficiency: a systematic review and meta-analysis - Ahmed M. Maged; Reham A. Mohsen; Noha Salah; Wael S. Ragab (BMC, 2024)
Abstract Objectives To assess the value of intraovarian PRP in women with low ovarian reserve. Search strategy Screening of databases from inception to January 2023 using the keywords related to "Platelet-rich plasma" AND "poor ovarian reserve" OR "ovarian failure". Selection criteria Fourteen studies (1632 participants) were included, 10 included women with POR, 1 included women with POI and 3 included both POR and POI women. Data collection and analysis Extracted data included study settings, design, sample size, population characteristics, volume, timing and preparation of PRP administration, and outcome parameters. Main results AMH level was evaluated in 11 studies (2099 women). The mean difference (MD) was 0.09 with 95% CI of - 0.06, 0.24 (P = 0.25). Antral follicular count level was assessed in 6 studies (1399 women). The MD was 1.73 with 95% CI of 0.81, 2.66 (P < 0.001). The number of oocytes retrieved was evaluated in 7 studies (1413 women). The MD was 1.21 with 95% CI of 0.48, 1.94 (P = 0.001). Conclusion This systematic review found a significant improvement of AFC, the number of retrieved oocytes, the number of cleavage embryos and the cancellation rate in women with POR. Trial registration Registration number CRD42022365682.